INFLUENCE OF ACTIVE MODIFICATION PARAMETERS ON BEARING CHARACTERISTICS OF OPPOSITE GEAR PAIRS (MT) - HOU YanYan; CHANG Qing; HU XiWen; PENG XianLong (Jixie qiangdu)
Active gear design is a method that can pre-control gear meshing performance directly. In order to study the influence of active gear design on the bearing characteristics of tooth surface, the relationship between active modification parameters of the face gear and bearing characteristics of tooth surface is studied. Firstly, the contact model of the gear pair is established by the finite element method, and then different groups of active modification parameters are designed for simulation analysis. The results show that the geometric transmission error greatly influences gear transmission stability and contact strength, and controlling its amplitude can control bearing transmission error amplitude. Pre-designed contact path inclination angle within 30° neighborhood, bearing contact characteristics are better. The contact ellipse length mainly affects the contact strength of tooth surface and bending strength of tooth root. According to the simulation results, when it takes 0.5～0.75 times of tooth width, face gear pair has better bearing contact characteristics.